In vitro activity of venoms Lachesis muta and Bothrops atroxSOBRE feasibility and embryonic development of eggs Ascaris suum - Paredes, Claudia (1999)
Snake venoms are polienzymatic concentrated whose biological activity on some bacteria and protozoa has been proven. To study the in vitro activity of Lachesis muta and B othrops atrox venoms on the viability and the development of Ascaris suum eggs is the main objecbve of this work. The venoms were employed in non embryonated and in vitro embryonated eggs of Ascaris suum at different concentrations (2, 4, 8,16 mg/mL). The activity of the venoms in the eggs and other substances like 5,25% sodium hypochlorite, Albendazol (commercial solution) and sodium chloride was compared. Both venoms, at 2, 4, 8, 16 mg/mL concentrations, inhibited segmentation of these eggs until the sixth day of incubation, when they began an apparently normal embryonation process that ended in the formation of the infective stage. The most effective inhibitory concentration was 16 mg/mL of B. atrox venom. The sodium hypochlorite destroyed 100% of eggs, while Albendazol produced abnormal segmentation process on them and their degeneration. We conclude that L. muta and B. atrox venoms have an inhibitory activity at the begining of segmentation in Ascaris suum eggs and they do not cause any effect on embryonated ones.